HYPOMORPHIC OVARIES IN METAPENAEUS MONOCEROS (FABRICIUS) - Nalini, C (Indian Journal of Fisheries, 2011)
The hypmaorpibic ovaries in three specimens of Metapenaeus monoceros (Fabrictns) obuuaed from Cochin waters during November 1973, are described. The abnormalities noticed pertain to the relatively undevelc^d state of the posterior lobe of the ovary in two specunens, and of the proximal ith region of the anterior lobe in a third one. Tbe probable causes for such aboormal development of the ovary are discussed.